2023
DOI: 10.31603/pharmacy.v9i1.6925
|View full text |Cite
|
Sign up to set email alerts
|

Direct Medical Cost and Length of Stay of Hypertension Patients at Private Hospital in Yogyakarta

Abstract: The province that ranks fourth with the highest incidence of hypertension in Indonesia is the Special Region of Yogyakarta (DIY). Hypertension therapy is carried out in a not short period, so it becomes an economic burden for people with hypertension and the government. This study aims to determine the relationship between the length of hospitalization and direct medical costs—an analytical observational research method with retrospective data collection and data from class III inpatient hypertensive medical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…10 Data from the Ministry of Health of the Republic of Indonesia showed that the costs of Social Security Agency on Health (the Badan Penyelenggara Jaminan Sosial or BPJS) in 2018 were absorbed mainly by treatment of chronic diseases such as diabetes, hypertension, and heart disease, with expenses reaching 6.67 trillion. 11 Previous studies revealed that the average cost of outpatient hypertensive patients was Indonesian Rupiah (IDR) 213,284 to IDR 434,632 per month. 12 Another study stated that the cost of the burden of disease due to hypertension in the community within Kediri District was IDR 330,882,930,485.…”
Section: Introductionmentioning
confidence: 99%
“…10 Data from the Ministry of Health of the Republic of Indonesia showed that the costs of Social Security Agency on Health (the Badan Penyelenggara Jaminan Sosial or BPJS) in 2018 were absorbed mainly by treatment of chronic diseases such as diabetes, hypertension, and heart disease, with expenses reaching 6.67 trillion. 11 Previous studies revealed that the average cost of outpatient hypertensive patients was Indonesian Rupiah (IDR) 213,284 to IDR 434,632 per month. 12 Another study stated that the cost of the burden of disease due to hypertension in the community within Kediri District was IDR 330,882,930,485.…”
Section: Introductionmentioning
confidence: 99%